2020
DOI: 10.1080/14767058.2020.1849124
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of confirmed COVID-19 in newborns: a systematic review

Abstract: Objective: Aim of this systematic review is to investigate the available evidence describing neonatal outcomes in newborns who have SARS-CoV-2 infection in order to guide prevention of COVID-19 in newborns. Methods: This is the study protocol for a systematic review. MEDLINE, Web of Science, PubMed, Science Direct, CINAHL, Scopus, Cochrane, TUB _ ITAK databases, and key words of "Newborn" (neonatal OR clinical characteristics newborn OR infants less than 1 month OR infants less than 28 weeks OR Neonate) AND "c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
5

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 50 publications
1
15
0
5
Order By: Relevance
“…This may be explained by the subjectivity of this symptom. Respiratory symptoms, i.e., cough, tachypnea, retractions, and rhinorrhea, were the main symptoms, as expected, similar to other adult and child series [17][18][19][20][21][24][25][26][27][28]. Among the respiratory symptoms, cough, retractions, and tachypnea on admission were independent predictors of more severe disease; however, this may be due to our use of the severity classification system of Dong et al [17].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This may be explained by the subjectivity of this symptom. Respiratory symptoms, i.e., cough, tachypnea, retractions, and rhinorrhea, were the main symptoms, as expected, similar to other adult and child series [17][18][19][20][21][24][25][26][27][28]. Among the respiratory symptoms, cough, retractions, and tachypnea on admission were independent predictors of more severe disease; however, this may be due to our use of the severity classification system of Dong et al [17].…”
Section: Discussionsupporting
confidence: 78%
“…However, neonates must be evaluated and treated differently from other children. There have been some neonatal case reports and series differing in severity [21]. In our cohort, we included neonates who required medical help, and were either symptomatic or had a contact history.…”
Section: Discussionmentioning
confidence: 99%
“…A review by Sheth et al reported a 30% prematurity rate in infected neonates [4]. Karabay et al in their systematic review found no significant relationship between birth weight and frequency of infection [23]. A lower mean birth weight with one-third being small for gestational age was probably due to a study being conducted in a public hospital catering to the low-middle class population with poor health-seeking behavior.…”
Section: Discussionmentioning
confidence: 98%
“…The first limitation of this study was that none of the neonates enrolled were tested for SARS-CoV-2 using nasopharyngeal swab after discharge. This information would have been epidemiologically important, as it has been reported that half of the neonates with SARS-CoV-2 infection may be asymptomatic (Karabay et al, 2020; Raschetti et al, 2020), so we cannot conclude that no newborn became positive for SARS-CoV-2 after discharge. The second limitation of this study was the failure to include late preterm and low birthweight infants, impairing the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 94%